Analysis of the Density of Electron-Hole Pairs for Minimal Pump Energy in a Laser Diode with Coherent Feedback - M. A. Grado-Caffaro; M. Grado-Caffaro (Active and Passive Electronic Components)
The average value in the time domain of the density of electron-hole pairs in a semiconductor laser with coherent feedback is calculated under conditions of minimal pump energy. This value is found to be finite; the significance of this result is discussed as well as the asymptotic value of the above carrier density.